2020
DOI: 10.1186/s43066-020-00037-9
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in Egyptian infants and children: risk factors, complications and outcome: a single center experience

Abstract: Background: The widespread use of abdominal ultrasonography in children documented increased detection rate of gallstones. The aim of this study was to assess the possible risk factors of gallstones and to detect the complication rate and outcome of the disease in Egyptian infants and children from a hepatologist perspective. This prospective study included 35 cases, with ultrasound-detected gallstones, who presented to the Pediatric Hepatology Unit from July 2015 to October 2017. All patients were initially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…3,4 In population based studies, the prevalence of cholelithiasis in children is about 1.9%. 3,5,6 Other study explain that this case's prevalence was 0.15-0.22 with male:female ratio are 2.3:1. Median age for boys was 5 years (3 months-14 years) and the median age for girl is 9 years (7 months-15 years).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…3,4 In population based studies, the prevalence of cholelithiasis in children is about 1.9%. 3,5,6 Other study explain that this case's prevalence was 0.15-0.22 with male:female ratio are 2.3:1. Median age for boys was 5 years (3 months-14 years) and the median age for girl is 9 years (7 months-15 years).…”
Section: Introductionmentioning
confidence: 80%
“…Idiopathic cholelithiasis, with no identifiable risk factors, has been reported for 23.2% -52.5%. 5 On the other hand comorbidities that are often found in cholelithiasis patients are hepatitis (30.8%), choledocholithiasis (16.9%), cholecystitis (16.9%), and acute pancreatitis (6.2%). 12 Acute pancreatitis was found through abdominal ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, age group 20-40 years had 10 males and 5 females, 40-60 years had 14 males and 12 females and >60 years had 20 males and 13 females. A group researcher found that the patients' ages ranged from 3.5 months up to 17 years (Enayet et al, 2020). The median age of gallstone detection was 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike adults, children are likely to be symptomatic, the prevalence of symptomatic children is from 50-70% [44]. The most common clinical presentation is right upper quadrant abdominal pain [usually after meals] which may be radiating to the right shoulder, nausea, vomiting and occasionally fever.…”
Section: Clinical Featuresmentioning
confidence: 99%